Cadmium Stress Leads to Rapid Increase in RNA Oxidative Modifications in Soybean Seedlings - Chmielowska-Bąk, Jagna; Izbiańska, Karolina; Ekner-Grzyb, Anna; Bayar, Melike; Deckert, Joanna (Frontiers in Plant Science, 2018)
Increase in the level of reactive oxygen species (ROS) is a common response to stress factors, including exposure to metals. ROS over-production is associated with oxidation of lipids, proteins and nucleic acids. It is suggested that the products of oxidation are not solely the markers of oxidative stress but also signaling elements. For instance it has been shown in animal models that mRNA oxidation is a selective process engaged in post-transcriptional regulation of genes expression and that it is associated with the development of symptoms of several neurodegenerative disorders. In the present study we examined the impact of short term cadmium stress on the level of two RNA oxidation markers: 8-hydroxyguanosine (8-OHG) and apuric/apirimidic sites (AP-sites, abasic sites). In the case of 8-OHG a significant increase was observed after 3 h of exposure to moderate Cd concentration (10 mg/l). In turn high level of AP-sites, accompanied by strong ROS accumulation and lipid peroxidation, was noted only after 24 h of treatment with higher Cd concentration (25 mg/l). This is the first report showing induction of RNA oxidations in plants response to stress factors. The possible signaling and gene regulatory role of oxidatively modified transcripts is discussed.